2012
DOI: 10.1534/genetics.112.143750
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Profiling of Disease Alleles Using a Tunable Reporter of Protein Misfolding

Abstract: Many human diseases are caused by genetic mutations that decrease protein stability. Such mutations may not specifically affect an active site, but can alter protein folding, abundance, or localization. Here we describe a high-throughput cell-based stability assay, IDESA (intra-DHFR enzyme stability assay), where stability is coupled to cell proliferation in the model yeast, Saccharomyces cerevisiae. The assay requires no prior knowledge of a protein's structure or activity, allowing the assessment of stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 54 publications
(70 reference statements)
1
31
0
Order By: Relevance
“…Besides an about 30-50% reduction in the catalytic efficiency of the transamination reaction [12,35], the protein encoded by the minor haplotype (AGT-Mi) mainly differs from that encoded by the major one (AGT-Ma) for a reduced thermodynamic and kinetic stability [12,16,18]. The P11L substitution has proven to be responsible for AGT-Mi destabilization because it raises the aggregation propensity of AGT expressed in bacteria [35,36], increases the susceptibility to proteolytic degradation [36], reduces yeast growth in complementation experiments [16,37], decreases the thermal denaturation midpoint of AGT in both the holo-and apo-forms, and destabilizes the dimeric structure of apoAGT in equilibrium denaturation studies [12,17,18]. Accordingly, differential scanning calorimetry analyses have shown that the kinetic stability of AGT drops by about 150-fold in the presence of the P11L polymorphism, while it increases by about 30-fold in the presence of the I340M polymorphism [17].…”
Section: Impact Of Polymorphic Substitutions On Agt Structure and Funmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides an about 30-50% reduction in the catalytic efficiency of the transamination reaction [12,35], the protein encoded by the minor haplotype (AGT-Mi) mainly differs from that encoded by the major one (AGT-Ma) for a reduced thermodynamic and kinetic stability [12,16,18]. The P11L substitution has proven to be responsible for AGT-Mi destabilization because it raises the aggregation propensity of AGT expressed in bacteria [35,36], increases the susceptibility to proteolytic degradation [36], reduces yeast growth in complementation experiments [16,37], decreases the thermal denaturation midpoint of AGT in both the holo-and apo-forms, and destabilizes the dimeric structure of apoAGT in equilibrium denaturation studies [12,17,18]. Accordingly, differential scanning calorimetry analyses have shown that the kinetic stability of AGT drops by about 150-fold in the presence of the P11L polymorphism, while it increases by about 30-fold in the presence of the I340M polymorphism [17].…”
Section: Impact Of Polymorphic Substitutions On Agt Structure and Funmentioning
confidence: 99%
“…On the other hand, the purification and characterization of the variants expressed in E. coli are suitable to dissect and quantify the effect of a mutation on the functional properties of AGT as well as on its secondary, tertiary and quaternary structures [11][12][13]17,18,35,36,[51][52][53][54][55][56][57][58]. Yeast and cell-free systems allow a rapid but semi-quantitative determination of the impact of each mutation on the intracellular activity, stability and assembly of the protein [37,53,54,59]. Thus, only the combination of more than one approach can provide a detailed picture of the molecular defect of a pathogenic variant.…”
Section: A Comprehensive Analysis Of the Molecular And Cellular Effecmentioning
confidence: 99%
“…For the remaining mutations the allele in which are present has not yet been identified. Expression analyses in E. coli, yeast and/or mammalian cellular systems of~60 PH1-related variants have allowed to establish differences in their kinetic behavior and/or coenzyme binding mode and affinity, degradation and/or aggregation propensity, expression level, thermodynamic and/or kinetic stability and subcellular localization [2,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Among the variants on the background of the minor allele, only G170R, F152I, G161S, G161C, G41R and I244T have been in depth characterized [13][14][15][16]18,22].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Adapting the present method for drug screening would allow candidate drugs to be tested for their potency. Such an assay could find a place alongside current models for drug screening in PH, such as yeast assays and mouse models [52,62, 63]. In addition to a qualitative assessment, this system could also allow a more quantitative description of the cellular mechanism of action (protein expression, catalytic activity, subcellular targeting) as has been done recently [30,48], as well as a direct assessment of oxalate and glyoxylate produced by the cells.…”
Section: Discussionmentioning
confidence: 99%